Rancang Bangun Sistem Monitoring Proses Layanan Pasang Baru Pada Pt. Telekomunikasi Indonesia Tbk. - Angga Wahyu Wicaksono; Tony Soebijono; Oktaviani Oktaviani (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
PT. Telkom Indonesia is one of biggest telecommunication company in Indonesia. Currently, there are 12 communication areas which support any kind of services from PT. Telkom. One of them is north Jawa Timur area. As the intention to give a good quality service for every customer, especially in north Jawa Timur area, PT. Telkom, however, sometimes finds an unexpected time management gap in installation process. To resolve and anticipate negative effects from that problem, PT. Telkom needs a monitoring system which can support their services.